2011
DOI: 10.5414/tep28049
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine (CAM) use in terminally ill patients

Abstract: Obiective: The use of complementary and alternative methods is common in oncology, but nothing is known about the role of CAM in the last days of a patient's life. Material and tnethods: Between 1-2007 and 10-2008 the palliative care teatn treated 85 patients (50 male, 35 female, median age 62 years) on out-door basis. All fatnilies were asked to complete a structured questionnaire regarding the use of CAM during the last period of the patient's life. Patients suffered from cancer in 83/85 patients (98%), 2 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…This difference was not observed in the measurements of the mandibular teeth, once again demonstrating that sodium selenite did not have a radioprotective action. This finding is in agreement with the study by Rocha et al (6), in which sodium selenite was not an effective radioprotector at 7 and 14 days of evaluation in bone tissue, but it is contrary to the outcomes of different studies (7,8,16,(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This difference was not observed in the measurements of the mandibular teeth, once again demonstrating that sodium selenite did not have a radioprotective action. This finding is in agreement with the study by Rocha et al (6), in which sodium selenite was not an effective radioprotector at 7 and 14 days of evaluation in bone tissue, but it is contrary to the outcomes of different studies (7,8,16,(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
“…Selenium is an essential nutrient for many species of animals, including humans (14). It is also a constituent of the peroxidase glutathione enzyme (6)(7), and this may be the explanation for its radioprotective effect. Selenium deficiency leads to a reduction in glutathione peroxidase activity (15) because it is considered an essential component of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auf die Bedeutung physiotherapeutischer Indikationen in der letzten Lebensphase deuten auch die Ergebnisse einer strukturierten schriftlichen Befragung der Familien schwerstkranker Palliativpatienten (n = 89) zu komplementären und alternativen Therapieansätzen hin: Rund ein Drittel der Erkrankten (n = 35) erhielten im terminalen Stadium Physiotherapie. Nach der spirituellen Begleitung zählten physiotherapeutische Interventionen zu den von den Befragten am hilfreichsten eingestuften komplementären Therapieansätzen [22].…”
Section: Indikationsbereicheunclassified
“…Selenium (Se), as a trace element necessary to maintain normal life activities of human body, has important physiological functions and a wide range of pharmacological effects (Buntzel et al, 2010;Handa et al, 2020;Hariharan & Dharmaraj, 2020;Razaghi et al, 2021). In recent years, a large number of studies have reported its role in tumor diagnosis and treatment, including various forms of selenium compounds such as inorganic selenium (Ganash, 2021), organic selenium (Gandin et al, 2018;Chuai et al, 2021), selenium metal complexes (Lai et al, 2019), and nano-selenium (Yu et al, 2015;Liu et al, 2021;Jiao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%